Managing Intellectual Property in Digital Environment through Digital Object Identifier (DOI) - Srivastava, Rochna (DESIDOC Journal of Library & Information Technology, 2003)
Paper discusses use of digital object identifier (DOI) for managing intellectual contents in a networked environment. Highlights components, features, aims, standards, and benefits of DOI. How DOI can be used in reference linking, citations and in print is discussed with examples. Stresses the need for building further features compatible with the existing implementation and emerging standard activities such as ISO, NISO, IETF, W3C, Dublin Core, Indecs, etc http://dx.doi.org/10.14429/dbit.24.2.3622